Everyday moral economies : food, politics and scale in Cuba - Wilson, Marisa L. (Marisa Lauren), 1979- (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2014)
"Offering a rare glimpse of rural life in modern-day Cuba, this book examines how ordinary Cubans carve out their own spaces for 'appropriate' acts of consumption, exchange, and production within the contradictory normative and material spaces of everyday economic life. Discusses the conflict between the socialist-welfare ideal of food as an entitlement and the market value of food as a commodity Bridges the fields of human geography and anthropology Approaches food networks and the scale of food systems in a novel way Provides a comprehensive look at Cuba today, with coverage of history, politics, economics, and social and environmental justice Enhanced by vivid photos from the field "--
"This book examines how ordinary people in Cuba carve out their own spaces for 2018appropriate' acts of consumption, exchange, and production within the contradictory normative and material spaces of everyday economic life"--
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Since 1990; Food supply -- Social aspects -- Cuba; Food supply -- Economic aspects -- Cuba; Consumption (Economics) -- Cuba; Exchange -- Cuba; Value; SCIENCE -- Earth Sciences -- Geography; Consumption (Economics); Economic history; Exchange; Food supply -- Economic aspects; Food supply -- Social aspects; Value; Cuba -- Economic conditions -- 1990-; Cuba; Electronic books